A method for preparing rubber additives using amino-functionalized graphene and rare earth compounds
By amino-functionalizing graphene oxide and reacting with rare earth compounds, an aerogel-like rubber additive was prepared, which solved the problem of graphene oxide agglomeration in rubber and significantly improved the mechanical properties and anti-aging properties of the rubber.
Patent Information
- Application Number
- CN202510093346.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-21
AI Technical Summary
Graphene oxide is prone to agglomeration in the rubber matrix, resulting in a decrease in the mechanical properties of the rubber and insufficient interface bonding with the rubber, affecting its anti-aging properties.
By aminofunctioning the graphene oxide and reacting with rare earth compounds under heating under oil bath, an aerogel-like rubber additive was prepared. The dispersion and interface binding force of graphene are improved through covalent linkage and coordination bond formation.
It significantly improves the tensile strength and tear strength of the rubber, enhances its anti-aging performance, and is simple and environmentally friendly.
Smart Images

Figure CN119505370B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of graphene nanomaterials and relates to a method for preparing a rubber additive by using amino-functionalized graphene and a rare earth compound. Background Art
[0002] Graphene (G) is a two-dimensional material with a single-layer carbon atom structure, which has excellent electrical conductivity, thermal conductivity and mechanical strength. Graphene oxide is a new type of carbon material with excellent performance. Compared with graphene (G), graphene oxide (GO) has the advantages of low production cost, large-scale production and easy processing. In addition, graphene oxide also has excellent properties such as high specific surface area and abundant active oxygen-containing functional groups. These oxygen-containing groups or reduced doping elements can be used as catalytic active centers and covalently / non-covalently modified and designed according to the requirements of specific application fields. In addition, the presence of oxygen-containing groups also widens the interlayer gap of graphene oxide, allowing graphene oxide to be functionalized by small molecules or polymer intercalation. Therefore, graphene oxide also shows excellent physical, chemical, optical and electrical properties, and because there are multiple oxygen-containing functional groups coexisting on the basal plane and edge of the graphene sheet skeleton, graphene oxide can modulate its conductivity and band gap by regulating the type and number of oxygen-containing functional groups contained. At present, great progress has been made in the functionalization research of graphene oxide. It has been applied in seawater desalination, drug delivery, oil-water separation, immobilized catalysis, solar cells, energy storage, healthcare and other fields.
[0003] However, due to its lamellar structure, graphene oxide (GO) is prone to agglomeration when added to the rubber matrix. This is because there are strong van der Waals forces between graphene oxide sheets, which makes it difficult to disperse them evenly in the rubber. This agglomerate is like a stress concentration point in the rubber. When the rubber is subjected to external force, the stress borne by the rubber molecular chains around the agglomerate will be much higher than that of other parts, which can easily cause the rubber to crack under low external force, thereby reducing the mechanical properties of the rubber such as tensile strength and tear strength. In addition, the interfacial bonding force between graphene oxide and the rubber matrix is weak. This is because the rubber molecular chain is mainly an organic chain segment composed of chemical bonds such as carbon-hydrogen, while the surface of graphene oxide contains a large number of oxygen-containing functional groups (such as hydroxyl, carboxyl, etc.). Due to the difference in the chemical structures of the two, the interaction between them is limited, which makes the graphene oxide have no obvious effect on the mechanical properties and anti-aging properties of rubber, and cannot improve other properties of rubber such as wear resistance and wetting properties.
[0004] At present, researchers have overcome the above problems by modifying graphene oxide, such as reacting graphene oxide with rare earth compounds for modification. However, when the two react, due to the interaction between the two and the difference in surface properties, rare earth particles will be unevenly distributed on the surface of graphene oxide, and agglomeration is likely to occur. The agglomerated rare earth particles will reduce the effective specific surface area of the product, affecting the performance of its performance, and will hinder the cross-linking of graphene and rubber after adding it as an additive to rubber, reducing the degree of cross-linking between the two. In addition, the interfacial bonding force between graphene oxide and rare earth is not strong enough, which will affect the stress transfer efficiency of the product when subjected to stress. When the prepared product is subjected to external force, interfacial debonding is likely to occur between graphene oxide and rare earth, resulting in a decrease in the mechanical properties of the material, thereby affecting the improvement of the performance of the rubber.
[0005] Therefore, in order to overcome the problems existing in the prior art, a patent application for the present invention is proposed. Summary of the invention
[0006] In view of the above technical problems, the present invention aims to provide a method for preparing a rubber additive using amino-functionalized graphene and a rare earth compound, which comprises preparing graphene oxide and amino-functionalized graphene in sequence, and then reacting the graphene with the rare earth compound under oil bath heating to obtain the rubber additive. The preparation method of the present invention is simple, the process is easy to control, the preparation raw materials do not involve toxic reagents, and the rubber additive is environmentally friendly. The prepared rubber additive is in the form of an aerogel. After being mixed and cross-linked with natural rubber, the tensile strength of the rubber can reach 70MPa. After thermal oxidation aging at 100°C for 72 hours, there are no cracks on the rubber surface, and the tensile strength can still reach 35MPa.
[0007] To achieve the above object, the technical solution adopted by the present invention is:
[0008] A method for preparing a rubber additive using amino-functionalized graphene and a rare earth compound is carried out in the following steps in sequence:
[0009] S1. Preparation of graphene oxide
[0010] Weigh 5g of 325 mesh flake graphite and 2g of NaNO3 in a reaction container and mix them evenly, then add 120mL of concentrated H2SO4, place it in a 0℃ ice bath and stir for 20~40min, add 20g of KMnO4 and react for 45~70min, then move it into a 40℃ warm water bath and continue to react for 20~40min, then slowly add 230mL of deionized water, and keep the reaction temperature at 85~98℃, stir for 5min, add H2O2 until no bubbles are generated, filter it while hot, and wash it with deionized water and 5% hydrochloric acid for several times until it is neutral, and then dry it in a 60℃ vacuum drying oven for 12~18h after washing to obtain graphene oxide;
[0011] S2. Preparation of amino-functionalized graphene
[0012] 0.26 g of graphene oxide was added to 150 mL of N,N-dimethylformamide to form a suspension, 0.32 g of (4-aminophenyl) tert-butyl carbamate was added to 20 mL of deionized water to form a (4-aminophenyl) tert-butyl carbamate aqueous solution, and then the suspension was added to the (4-aminophenyl) tert-butyl carbamate aqueous solution, and the reaction was carried out at 120 ° C on a magnetic heating stirrer for 13 to 19 hours. After the reaction, the sample was cooled to room temperature, and 23 mL of trifluoroacetic acid was added, and the magnetic heating stirrer was continued to stir at room temperature for 4 to 6 hours, and then the product was spin-dried using a rotary evaporator, and the product was centrifugally washed with anhydrous ethanol and deionized water for 3 to 8 times, respectively, and then the sample was freeze-dried using a vacuum freeze dryer to obtain amino-functionalized graphene;
[0013] S3. Preparation of rubber additives
[0014] After the amino-functionalized graphene and cerium nitrate are blended by ultrasonication, ammonia water is added dropwise to adjust the pH to weak alkalinity, and then the mixture is transferred to a round-bottom flask and heated and stirred in an oil bath at 80-105°C at a speed of 260-400 r / min for 9-15 hours. The product is then centrifugally washed with anhydrous ethanol and deionized water for 3-8 times, respectively, and then freeze-dried using a vacuum freeze dryer to obtain a rubber additive.
[0015] The present invention uses (4-aminophenyl) tert-butyl carbamate to modify graphene oxide. Since the (4-aminophenyl) tert-butyl carbamate molecule is relatively large, a uniformly distributed interlayer structure can be formed on the surface of graphene oxide after grafting, so that graphene layers are not easy to agglomerate, thereby greatly improving the dispersibility of graphene oxide. In addition, the amino group itself has strong hydrophilicity. When the amino group is modified on the surface of graphene oxide, the amino group can form hydrogen bonds with water molecules, thereby increasing the dispersibility of graphene oxide in an aqueous environment. In addition, since (4-aminophenyl) carbamate has different amino groups at both ends, one end of the amino group can react with the carboxyl group on the surface of graphene oxide to undergo amidation reaction. Under appropriate conditions, the carboxyl group (-COOH) reacts with the amino group (-NH2) to form an amide bond (-CONH-). The amino group (-NH2) can also react with the epoxy group (-CH(O) CH-) to form a β-hydroxyamino group (-NH-CC-OH). The formation of this chemical bond changes the surface chemical composition of graphene oxide. The reaction formulas are: R-COOH+R'-NH2 → R-CONH-R' +H2O, R1-CH (O) CH-R2 +R'-NH2 →R1 -CH- (NHR') - CH(OH) - R2 (where R1, R2 and R' represent organic groups, which represent the partial structure of graphene oxide and the remaining structure of the amino compound in the reaction between graphene oxide and amino compounds, respectively). This covalent connection is more stable than non-covalent connection, so the organic molecule is not easy to fall off, and the amino group on the other end of (4-aminophenyl) tert-butyl carbamate is an amino group protected by the BOC method, which ensures that the amino group will not be consumed by the functional groups on graphene oxide. After obtaining the initial reaction product, it is de-BOC treated with trifluoroacetic acid to expose the protected amino group for the next reaction. Through this reaction, the newly introduced amino group and its connected partial structure increase the types and number of functional groups on the surface of graphene oxide, thereby improving its surface activity, dispersibility and hydrophilicity. In addition, the nitrogen atom in the introduced amino group has a lone pair of electrons, which can act as a ligand to form a coordination bond with the cerium ion. The cerium ion has an empty orbital and can accept the lone pair of electrons provided by the amino nitrogen atom, thereby realizing the combination of the two. This binding mode is relatively stable and reversible under certain conditions. The formation and breaking of the coordination bond can be regulated by changing environmental conditions such as pH, temperature, etc., and the addition of cerium ions can improve the catalytic performance of amino-functionalized graphene, optimize its electrochemical properties, improve dispersibility and enhance the antibacterial properties of amino-functionalized graphene.
[0016] In the present invention, the addition of cerium ions can not only improve the antioxidant property of amino-functionalized graphene, enhance its surface activity, and prevent the agglomeration of amino-functionalized graphene, but also can be loaded on amino-functionalized graphene and added to natural rubber to promote the vulcanization of natural rubber, and enhance the mechanical properties and anti-aging properties of natural rubber. Since cerium ions have variable valence states, they can play the role of electron transfer and storage in redox reactions, thereby effectively removing free radicals on the surface of amino-functionalized graphene, preventing it from further oxidation, thereby improving the antioxidant property of the material, and cerium ions can interact with functional groups such as amino groups on the surface of amino-functionalized graphene to form new active sites, which can adsorb and activate reactant molecules, reduce the activation energy of the reaction, thereby improving the rate and efficiency of the catalytic reaction, in addition, there are electrostatic interactions, hydrogen bonds or chemical bonds between cerium ions and amino-functionalized graphene, which can effectively prevent the agglomeration between graphene sheets, so that it has better dispersibility in solutions or composite materials, and the interface between each component is more closely combined, thereby improving the comprehensive performance of the material.
[0017] As a limitation of the preparation method of the present invention, in step S2, the stirring rate of the magnetic heating stirrer is 300-560 r / min.
[0018] As a second limitation of the preparation method of the present invention, in step S2, the spin drying temperature is 60-85° C., and the rotation speed is 55-80 r / min.
[0019] As a third limitation of the preparation method of the present invention, in step S2, the centrifugal speed during the centrifugal washing process is 8000-12000 r / min, and the time is 8-20 min.
[0020] As a fourth limitation of the preparation method of the present invention, in step S2, the freeze-drying temperature is -55 to -36°C, and the time is 24 to 48 hours.
[0021] As a fifth limitation of the preparation method of the present invention, in step S3, the mass ratio of the amino-functionalized graphene to cerium nitrate is 1:1.
[0022] In the present invention, the mass ratio of amino-functionalized graphene to cerium nitrate is crucial. If the mass ratio is greater than 1:1, too much cerium ion is attached to the graphene surface, the surface amino functional groups are consumed too much and the dispersion is poor, so that the crosslinking degree between the amino group and the rubber is greatly reduced, resulting in a poor reinforcement effect on the rubber. If the mass ratio is less than 1:1, the loading amount of cerium ion on the surface of amino-functionalized graphene is too small, resulting in less participation of cerium ion in rubber crosslinking, and rare earth cerium cannot participate in the crosslinking reinforcement reaction of the rubber, so that the reinforcement effect does not meet the theoretical expectation.
[0023] As a sixth limitation of the preparation method of the present invention, in step S3, the mass concentration of the ammonia water is 25%, and the pH value of the solution is 8.5.
[0024] In the present invention, the pH value of the solution will affect the loading of the amino-functionalized graphene on the cerium ions. If the solution is acidic, the tetravalent ions of cerium nitrate are active and oxidizing, and the amino functional groups coordinated on the graphene surface are easily oxidized to lose the amino characteristics. In addition, the tetravalent cerium ions are most often expressed as cerium oxide, which is insoluble in water and appears as a white precipitate. This makes it impossible for the cerium ions to be loaded on the amino-functionalized graphene. However, the cerium ions are easily hydrolyzed under strong alkaline conditions to generate basic salt precipitation. Therefore, the pH value of the reaction solution system must be adjusted to a weak alkalinity of 8.5 before the cerium ions are loaded on the graphene. Ammonia water is weakly alkaline, and ammonia water has amino functional groups and will not affect the reaction.
[0025] As the seventh limitation of the preparation method of the present invention, in step S3, the centrifugal speed during the centrifugal washing process is 8000-12000 r / min, and the time is 8-15 min.
[0026] As an eighth limitation of the preparation method of the present invention, the freeze-drying temperature is -55 to -36°C, and the time is 24 to 40 hours.
[0027] The present invention effectively realizes the covalent connection between the organic functional molecule and graphene by the nucleophilic ring-opening reaction between the amino group in (4-aminophenyl) tert-butyl carbamate and the epoxy group in graphene oxide, and further effectively removes the Boc protecting group tert-butyl carbamate by trifluoroacetic acid to obtain amino covalent functionalized graphene, which is more stable than non-covalent connection, so the organic molecule is not easy to fall off. Although the experimental process occurs in two steps, it is achieved by a simple one-pot method, and the amino functionalized graphene can effectively control the content of the amino group, realizing the regulation of the reaction of two amino groups on the same molecule that cannot be achieved by traditional methods, and effectively controlling the reaction of the amino group on the functionalized reagent (one amino group undergoes a nucleophilic ring-opening reaction with graphene oxide for covalent connection, and one provides functionality for graphene through protection removal), and the amino functionalized graphene obtained in this way has good dispersibility. In addition, the amino groups of amino-functionalized graphene can be combined with cerium ions. The amino groups provide electron pairs and the metal ions provide empty orbitals. The two attract and coordinate each other. The cross-linking effect of the amino groups, the strengthening effect of graphene oxide and the strengthening effect of cerium ions on the binding force cooperate with each other. The cross-linking network formed by the amino groups makes the rubber molecular chains tightly connected. Graphene oxide plays a role in strengthening the skeleton, and cerium ions strengthen the bonding between the components, so that the rubber can more effectively transmit and disperse stress when subjected to external forces, and jointly improve the mechanical properties of rubber such as tensile strength, tear strength and elastic modulus. In addition, the effects of amino groups capturing free radicals, graphene oxide blocking aging media and cerium ions consuming active oxygen work together. The amino groups capture free radicals inside the rubber, cerium ions consume active oxygen on the surface and inside the rubber, and graphene oxide prevents the entry of external aging media, forming an anti-aging system from the inside to the outside, greatly delaying the aging process of rubber and improving the durability of rubber.
[0028] After the rubber additive prepared by the present invention is added to rubber, since there is a pair of lone pairs of electrons on the nitrogen atom of the amino functional group in the amino functionalized graphene, the amino group can react with sulfur during the vulcanization process of the natural rubber. When the amino-containing compound is used as a vulcanization aid, it can increase the crosslinking density of the natural rubber at a lower vulcanization temperature and a shorter vulcanization time. At this time, since the amino group can activate the vulcanization reaction, the double bonds in the rubber molecular chain are more likely to react with the vulcanizing agent, thereby accelerating the vulcanization process. In addition, since the amino group promotes the crosslinking reaction, a tighter three-dimensional network structure is formed between the rubber molecular chains. Such a structure can effectively disperse external forces. When the rubber product is subjected to tensile or tearing forces, the crosslinking bonds can prevent the molecular chains from slipping, thereby improving the tensile strength and tearing strength of the vulcanized rubber. Cerium ions have empty orbitals and can form coordination bonds with sulfur atoms in the rubber vulcanization system, reduce the activation energy of the reaction, speed up the vulcanization reaction, and improve the vulcanization efficiency. Cerium ions can interact strongly with rubber molecular chains, restrict the movement of molecular chains, and bear more external forces, thereby improving the mechanical properties of rubber such as tensile strength, tear strength, hardness, and wear resistance. In addition, cerium ions can also coordinate with some active groups on the rubber molecular chains, and can also be adsorbed on the surface of graphene oxide. This interaction can enhance the binding force between the rubber matrix, amino groups and graphene oxide. When subjected to external forces, this good binding force can enable them to work together to better resist external forces and further improve the mechanical properties of rubber. Cerium ions can also capture free radicals generated by natural rubber during use due to heat, oxygen, light and other factors, prevent chain reactions caused by free radicals, prevent the breakage of rubber molecular chains and the destruction of cross-linked structures, thereby delaying the aging process of rubber.
[0029] The above technical solution of the present invention is taken as a whole, and each step is closely related and influences each other, which jointly determine the morphological characteristics and performance of the product.
[0030] The above technical solution has the following advantages or beneficial effects:
[0031] 1. The rubber additive prepared by the present invention is in the form of aerogel. After being added to rubber, the rubber tensile strength can reach up to 70MPa. After 72h of thermal oxidative aging, there is no crack on the rubber surface, and the tensile performance can still reach 34.66MPa.
[0032] 2. The rubber additive prepared by the present invention can effectively prevent the aggregation of graphene sheets after the additive is added to natural rubber due to the interaction between amino-functionalized graphene and cerium ions, thereby enhancing its dispersibility and firming the interface bonding, thereby enhancing the mechanical properties and anti-aging properties of natural rubber;
[0033] 3. The preparation method of the present invention is simple, the process is easy to control, requires little equipment, does not involve toxic solvents, and is environmentally friendly.
[0034] The invention is suitable for preparing rubber additives.
[0035] The technical solution of the present invention will be further described in detail below in conjunction with the accompanying drawings and specific implementation methods. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a scanning electron microscope image of the amino-functionalized graphene prepared in Example 1 of the present invention;
[0037] Figure 2 This is an infrared spectrum of the amino-functionalized graphene prepared in Example 1 of the present invention;
[0038] Figure 3 This is an EDS energy dispersive X-ray spectrometer surface scan of the rubber additive prepared in Example 2 of the present invention;
[0039] Figure 4 This is a Raman spectrum of the rubber additive prepared in Example 2 of the present invention;
[0040] Figure 5 The mechanical properties diagram of the rubber additives prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 3 are shown. DETAILED DESCRIPTION
[0041] The following embodiments are only some embodiments of the present invention, rather than all embodiments. Therefore, the detailed description in the embodiments of the present invention provided below is not intended to limit the scope of the present invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work belong to the protection scope of the present invention.
[0042] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments are all conventional methods in the art unless otherwise specified. Example 1
[0043] This embodiment prepares a rubber additive, and its preparation process and steps are as follows:
[0044] S1. Preparation of graphene oxide
[0045] Weigh 5g of 325 mesh flake graphite and 2g of NaNO3 in a reaction container and mix them evenly, add 120mL of concentrated H2SO4, place it in a 0℃ ice bath and stir for 30min, add 20g of KMnO4 and react for 60min, move it into a 40℃ warm water bath and continue to react for 30min, then slowly add 230mL of deionized water, and keep the reaction temperature at 98℃, stir for 5min, add H2O2 until no bubbles are generated, filter it while hot, and wash it with deionized water and 5% hydrochloric acid for several times until it is neutral, and dry it in a 60℃ vacuum drying oven for 12h after washing to obtain graphene oxide;
[0046] S2. Preparation of amino-functionalized graphene
[0047] 0.26 g of graphene oxide was added to 150 mL of N, N-dimethylformamide to form a suspension, 0.32 g of (4-aminophenyl) tert-butyl carbamate was added to 20 mL of water to form a (4-aminophenyl) tert-butyl carbamate aqueous solution, and then the suspension was added to the (4-aminophenyl) tert-butyl carbamate aqueous solution, heated and stirred at a stirring rate of 500 r / min for 18 h on a magnetic heating stirrer, and the temperature was controlled at 120 ° C. After the reaction, the sample was cooled to room temperature, and 23 mL of trifluoroacetic acid was added, and the stirring rate of 500 r / min was continued to be stirred at room temperature for 5 h using a magnetic heating stirrer, and then the sample was dried by rotary evaporation at a temperature of 80 ° C and a speed of 80 r / min, and the product was centrifuged and washed at 12000 r / min for 10 min with anhydrous ethanol and deionized water, respectively, for 6 times, and then the sample was freeze-dried at -36 ° C for 24 h using a vacuum freeze dryer to obtain amino-functionalized graphene;
[0048] S3. Preparation of rubber additives
[0049] After ultrasonically blending 3.5 g of amino-functionalized graphene and 3.5 g of cerium nitrate, the pH value of the solution was adjusted to 8.5 using 25% ammonia water, and then transferred to a round-bottom flask, stirred at 360 r / min in an oil bath and heated at 90°C for 12 h. The product was then centrifuged and washed with anhydrous ethanol and deionized water at 12000 r / min for 10 min, centrifuged 6 times, and then freeze-dried at -36°C for 24 h using a vacuum freeze dryer to obtain a rubber additive.
[0050] The additive prepared in this example was characterized. Figure 1 , is a scanning electron microscope image of the amino-functionalized graphene prepared in this example. From the image, it can be seen that the surface of the amino-functionalized graphene is rough and has tentacles, the interlayer distribution is uniform, there are no large particles, no abnormal bubbles and voids, and no agglomeration.
[0051] like Figure 2 , is the infrared spectrum of the amino-functionalized graphene prepared in Example. It can be seen from the figure that the amino-functionalized graphene is successfully grafted with amino functional groups, and no abnormal peaks are generated. Example 2
[0052] This embodiment prepares a rubber additive, and its preparation process and steps are as follows:
[0053] S1. Preparation of graphene oxide
[0054] Weigh 5g of 325 mesh flake graphite and 2g of NaNO3 in a reaction container and mix them evenly, add 120mL of concentrated H2SO4, and place it in a 0℃ ice bath and stir for 20min. Add 20g of KMnO4 and react for 45min, then move it into a 40℃ warm water bath and continue to react for 20min, then slowly add 230mL of deionized water, and keep the reaction temperature at 90℃. After stirring for 5min, add H2O2 until no bubbles are generated, filter it while hot, and wash it with deionized water and 5% hydrochloric acid for several times until it is neutral. After washing, dry it in a 60℃ vacuum drying oven for 15h to obtain graphene oxide;
[0055] S2. Preparation of amino-functionalized graphene
[0056] 0.26 g of graphene oxide was added to 150 mL of N, N-dimethylformamide to form a suspension, 0.32 g of (4-aminophenyl) tert-butyl carbamate was added to 20 mL of water to form a (4-aminophenyl) tert-butyl carbamate aqueous solution, and then the suspension was added to the (4-aminophenyl) tert-butyl carbamate aqueous solution, heated and stirred at a stirring rate of 300 r / min for 13 h on a magnetic heating stirrer, and the temperature was controlled at 120 ° C. After the reaction, the sample was cooled to room temperature, and 23 mL of trifluoroacetic acid was added, and the stirring rate of 300 r / min was continued to be stirred at room temperature for 4 h using a magnetic heating stirrer, and then the sample was dried by rotary evaporation at a temperature of 60 ° C and a speed of 65 r / min, and the product was centrifuged and washed at 10000 r / min for 8 min with anhydrous ethanol and deionized water respectively, and washed 8 times, and then the sample was freeze-dried at -40 ° C for 32 h using a vacuum freeze dryer to obtain amino-functionalized graphene;
[0057] S3. Preparation of rubber additives
[0058] After ultrasonically blending 3.5 g of amino-functionalized graphene and 3.5 g of cerium nitrate, the pH value of the solution was adjusted to 8.5 using 25% ammonia water, and then transferred to a round-bottom flask, stirred at 260 r / min in an oil bath and heated at 80°C for 9 h. The product was then centrifuged and washed with anhydrous ethanol and deionized water at 10,000 r / min for 8 min, centrifuged 8 times, and then freeze-dried at -40°C for 30 h using a vacuum freeze dryer to obtain a rubber additive.
[0059] The additive prepared in this example was characterized. Figure 3 , is an EDS energy dispersive X-ray spectrometer surface scanning (Energy-Dispersive X-Ray Spectroscopy Mapping) diagram of the rubber additive prepared in this embodiment. It can be seen from the figure that the cerium ions are evenly and densely distributed on the surface of the amino-functionalized graphene, without agglomeration and abnormal structural voids.
[0060] like Figure 4 , is the Raman spectrum of the rubber additive prepared in this example. It can be seen from the figure that the ratio of the G peak to the D peak is normal, there is no abnormal peak shape, and no impurity peak is generated, indicating that the addition of cerium ions has no effect on the structure and functional groups of the amino-functionalized graphene. Example 3
[0061] This embodiment prepares a rubber additive, and its preparation process and steps are as follows:
[0062] S1. Preparation of graphene oxide
[0063] Weigh 5g of 325 mesh flake graphite and 2g of NaNO3 in a reaction container and mix them evenly, add 120mL of concentrated H2SO4, place it in a 0℃ ice bath and stir for 40min, add 20g of KMnO4 and react for 70min, move it into a 40℃ warm water bath and continue to react for 40min, then slowly add 230mL of deionized water, and keep the reaction temperature at 85℃, stir for 5min, add H2O2 until no bubbles are generated, filter it while hot, and wash it with deionized water and 5% hydrochloric acid for several times until it is neutral, and dry it in a 60℃ vacuum drying oven for 18h after washing to obtain graphene oxide;
[0064] S2. Preparation of amino-functionalized graphene
[0065] 0.26 g of graphene oxide was added to 150 mL of N, N-dimethylformamide to form a suspension, 0.32 g of (4-aminophenyl) tert-butyl carbamate was added to 20 mL of water to form a (4-aminophenyl) tert-butyl carbamate aqueous solution, and then the suspension was added to the (4-aminophenyl) tert-butyl carbamate aqueous solution, heated and stirred at a stirring rate of 560 r / min for 19 h on a magnetic heating stirrer, and the temperature was controlled at 120 ° C. After the reaction, the sample was cooled to room temperature, and 23 mL of trifluoroacetic acid was added, and the stirring rate of 560 r / min was continued to be stirred at room temperature for 6 h using a magnetic heating stirrer, and then the sample was spin-dried at a temperature of 85 ° C and a speed of 55 r / min using a rotary evaporator, and the product was centrifuged and washed at 8000 r / min for 20 min with anhydrous ethanol and deionized water respectively, and washed 3 times, and then the sample was freeze-dried at -55 ° C for 48 h using a vacuum freeze dryer to obtain amino-functionalized graphene;
[0066] S3. Preparation of rubber additives
[0067] After ultrasonically blending 3.5 g of amino-functionalized graphene and 3.5 g of cerium nitrate, the pH value of the solution was adjusted to 8.5 using 25% ammonia water, and then transferred to a round-bottom flask, stirred at 400 r / min in an oil bath and heated at 105°C for 15 h. The product was then centrifuged and washed with anhydrous ethanol and deionized water at 8000 r / min for 15 min, centrifuged 3 times, and then freeze-dried at -55°C for 40 h using a vacuum freeze dryer to obtain a rubber additive. Comparative Example
[0068] In order to explore the effects of different parameters and different substances in the preparation process of the present invention on the performance of the product of the present invention, the following comparative experiments were conducted. Different composites were prepared in the following comparative examples, as follows:
[0069] Comparative Example 1
[0070] Different rubber additives were prepared in this comparative example. The preparation method was similar to that in Example 1, except that in step S3, the mass ratio of amino-functionalized graphene to cerium nitrate was different, as follows:
[0071] Group A: The mass ratio of amino-functionalized graphene to cerium nitrate was 1:0.5;
[0072] Group B: The mass ratio of amino-functionalized graphene to cerium nitrate was 1:2;
[0073] Group C: The mass ratio of amino-functionalized graphene to cerium nitrate was 1:5;
[0074] Group D: The mass ratio of amino-functionalized graphene to cerium nitrate was 1:8;
[0075] Group E: The mass ratio of amino-functionalized graphene to cerium nitrate was 1:10;
[0076] Group F: The mass ratio of amino-functionalized graphene to cerium nitrate is 1:15.
[0077] Comparative Example 2
[0078] In this comparative example, a rubber additive is prepared. The preparation process is similar to that of Example 1, except that in step S3, cerium nitrate is not added. The remaining steps and parameters are the same as those of Example 1.
[0079] Comparative Example 3
[0080] In this comparative example, a rubber additive is prepared. The preparation process is similar to that of Example 1, except that step S2 is not performed, that is, the graphene oxide prepared in step S1 is directly compounded with cerium nitrate.
[0081] Performance Testing
[0082] 2.5 g of the additives prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were weighed respectively, and were mixed evenly with 50 g of natural rubber, 1 g of vulcanization accelerator M (2-mercaptobenzothiazole), 2.5 g of vulcanization activator zinc oxide ZnO, 1 g of surfactant stearic acid (octadecanoic acid), and 1 g of antioxidant 4010NA (N-isopropyl-N'-phenyl-p-phenylenediamine) and added to a mixer, and mixed for 30 min at a speed of 100 r / min and a temperature of 60°C, and then the mixer was stopped from heating, 1.5 g of vulcanizing agent sulfur was added at room temperature and continued to mix for 5 min, and the mixing speed was 150 r / min, and then the rubber material was vulcanized for 5 min at 160°C and a pressure of 10 MPa. After the vulcanization was completed, the rubber product was cooled to make it cool down and solidify quickly to keep the shape and size stable, and then a dumbbell-shaped sample was cut out by a dumbbell-shaped cutter for mechanical property test and anti-aging property test.
[0083] (1) Mechanical properties characterization
[0084] like Figure 5As can be seen from the figure, after the rubber additives prepared in Examples 1 to 3 are added to the rubber, the tensile strength of the rubber is 67.72MPa, 69.38MPa, and 70.26MPa, respectively, while after the rubber additives in Groups A to F of Comparative Example 1 are added to the rubber, the rubber tensile strength is 19.84 to 62.33MPa. When the rubber additives in Comparative Examples 2 to 3 are added to the rubber, the tensile strengths thereof are only 42.34MPa and 31.27MPa, and the tensile strength of pure natural rubber is only 12MPa. Therefore, it is fully demonstrated that after the rubber additives prepared in the present invention are added to the rubber, the mechanical properties of the natural rubber can be greatly improved.
[0085] (2) Characterization of anti-aging performance
[0086] The above different rubber samples were placed in a 100°C oven for thermal oxidation aging for 72 hours and then subjected to tensile testing. The test results are shown in the following table:
[0087]
[0088] In summary, the rubber additive prepared by the present invention greatly enhances the mechanical properties of natural rubber after mixing with natural rubber and vulcanization through the synergistic network cross-linking effect among amino functional groups, graphene oxide and cerium ions. The isolated electron pairs of the amino functional groups and the variable valence states of the cerium ions can play a role in electron transfer and storage in the redox reaction, thereby effectively removing free radicals on the surface of amino-functionalized graphene, preventing its further oxidation, and improving the anti-aging performance of natural rubber.
[0089] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein with equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a rubber additive using amino-functionalized graphene and a rare earth compound, characterized in that: Follow the steps below in order: S1. Preparation of graphene oxide Weigh 5g of 325 mesh flake graphite and 2g of NaNO3 in a reaction container and mix them evenly, then add 120mL of concentrated H2SO4, place it in a 0℃ ice bath and stir for 20~40min, add 20g of KMnO4 and react for 45~70min, then move it into a 40℃ warm water bath and continue to react for 20~40min, then slowly add 230mL of deionized water, and keep the reaction temperature at 85~98℃, stir for 5min, add H2O2 until no bubbles are generated, filter it while hot, and wash it with deionized water and 5% hydrochloric acid for several times until it is neutral, and then dry it in a 60℃ vacuum drying oven for 12~18h after washing to obtain graphene oxide; S2. Preparation of amino-functionalized graphene 0.26 g of graphene oxide was added to 150 mL of N,N-dimethylformamide to form a suspension, 0.32 g of (4-aminophenyl) tert-butyl carbamate was added to 20 mL of deionized water to form a (4-aminophenyl) tert-butyl carbamate aqueous solution, and then the suspension was added to the (4-aminophenyl) tert-butyl carbamate aqueous solution, and the reaction was carried out at 120 ° C on a magnetic heating stirrer for 13 to 19 hours. After the reaction, the sample was cooled to room temperature, and 23 mL of trifluoroacetic acid was added, and the magnetic heating stirrer was continued to stir at room temperature for 4 to 6 hours, and then the product was spin-dried using a rotary evaporator, and the product was centrifugally washed with anhydrous ethanol and deionized water for 3 to 8 times, respectively, and then the sample was freeze-dried using a vacuum freeze dryer to obtain amino-functionalized graphene; S3. Preparation of rubber additives After the amino-functionalized graphene and cerium nitrate were ultrasonically blended in a mass ratio of 1:1, 25% ammonia water was added dropwise to adjust the pH to 8.5, and then the mixture was transferred to a round-bottom flask, heated and stirred in an oil bath at 80-105°C at a speed of 260-400 r / min for 9-15 hours, and then the product was centrifugally washed with anhydrous ethanol and deionized water for 3-8 times, respectively, and then the sample was freeze-dried using a vacuum freeze dryer to obtain a rubber additive.
2. The method for preparing a rubber additive using amino-functionalized graphene and a rare earth compound according to claim 1, characterized in that: In step S2, the stirring rate of the magnetic heating stirrer is 300-560 r / min.
3. The method for preparing a rubber additive using amino-functionalized graphene and a rare earth compound according to claim 1, characterized in that: In step S2, the spin drying temperature is 60-85°C and the rotation speed is 55-80r / min.
4. The method for preparing a rubber additive using amino-functionalized graphene and a rare earth compound according to claim 1, characterized in that: In step S2, the centrifugal speed during the centrifugal washing process is 8000-12000 r / min, and the time is 8-20 min.
5. The method for preparing a rubber additive using amino-functionalized graphene and a rare earth compound according to claim 1, characterized in that: In step S2, the freeze-drying temperature is -55 to -36°C and the time is 24 to 48 hours.
6. The method for preparing a rubber additive using amino-functionalized graphene and a rare earth compound according to claim 1, characterized in that: In step S3, the centrifugal speed during the centrifugal washing process is 8000-12000 r / min, and the time is 8-15 min.
7. The method for preparing a rubber additive using amino-functionalized graphene and a rare earth compound according to claim 1, characterized in that: In step S3, the freeze-drying temperature is -55 to -36°C and the time is 24 to 40 hours.
Citation Information
Patent Citations
Rare earth element labeled graphene oxide nanosheet as well as preparation method and application thereof
CN111517316A
Functionalized graphene, preparation method and application thereof, and preparation of rubber composite material
CN116987325A